Partial support for ZNF804A genotype‐dependent alterations in prefrontal connectivity1. Issue 2 (31st October 2011) - Paulus, Frieder M.; Krach, Sören; Bedenbender, Johannes; Pyka, Martin; Sommer, Jens; Krug, Axel; Knake, Susanne; Nöthen, Markus M.; Witt, Stephanie H.; Rietschel, Marcella; Kircher, Tilo; Jansen, Andreas
Abstract Genome‐wide association studies identified the single nucleotide polymorphism rs1344706 in ZNF804A as a common risk‐variant for schizophrenia and bipolar disorder. Whereas the molecular function of ZNF804A is yet unclear, recent imaging genetics studies have started to characterize the neural systems architecture linking rs1344706 genotype to psychosis. Carring rs1344706 risk‐alleles was associated with a decrease in functional connectivity within the dorsolateral prefrontal cortices (DLPFCs) as well as an increase in connectivity between the DLPFC and the hippocampal formation (HF) in the context of a working memory task. The present study aimed at replicating these findings in an independent sample of 94 healthy subjects. Subjects were genotyped for rs1344706 and performed a working memory task during functional magnetic resonance imaging. Results indicate no support for a decrease of functional coupling between the bilateral DLPFCs at higher ZNF804A risk status. However, the current data show the previously described alteration in functional coupling between the right DLPFC and the HFs, albeit with weaker effects. Decoupled by default, the functional connectivity between the right DLPFC and anterior HFs increased with the number of rs1344706 risk alleles. The present data support fronto‐hippocampal dysconnectivity as intermediate phenotype linking rs1344706 genotype to psychosis. We discuss the issues in replicating the interhemispheric DLPFC coupling in light of the effect sizes rs1344706 genotype has on brain function, concluding that further independent replication studies are fundamentally needed to ascertain the role of rs1344706 in the functional integration of neural systems. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.